Analisis Persepsi dan Kinerja dalam Peningkatakan Kinerja Pengawasan di Pangkalan Pengawasan Sumberdaya Kelautan dan Perikanan Tual - Bintoro, Sigit; Riani, Etty; Rumanta, Maman (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The effectiveness of supervision is a key factor in preserving resources and preventing illegal actions that are detrimental to the state, so it is necessary to look for strategies to improve the performance of supervisors at the Tual PSDKP Base which is important in eradicating IUU Fishing. This research will support government policies in preventing and enforcing laws, as well as maintaining the sustainability of fisheries resources and marine ecosystems. This research aims to formulate a strategy to improve the performance of marine and fisheries resource supervisors at the Tual Marine and Fisheries Resources Monitoring Base (PSDKP). This research uses performance analysis and perception analysis using a descriptive approach. To determine the reliability of the data in performance analysis and perception analysis of the questionnaire results, validity and reliability tests were carried out. The results of the performance analysis show that the Tual PSDKP Base has carried out supervision activities well as seen from the performance achievements that have been determined, however, according to the results of the analysis of perceptions from respondents, improvements still need to be made to support supervision activities optimally, namely by developing and increasing human resource competency, as well as providing adequate monitoring facilities and infrastructure. The implementation of these strategies is expected to increase the effectiveness of supervision, reduce violations, and support the sustainability of marine and fisheries resources in the Tual PSDKP Base area.